Increase of Citric Acid Production by Aspergillus niger InaCC F539 in Sorghum’s Juice Medium Amended with Methanol - Kanti, Atit; Ilyas, Muhammad; Sudiana, I Made (Perhimpunan Biologi Indonesia, 2018)
ABSTRACTCitric acid demand increases steadily, and there is a need to increase productivity through selection of suitable carbon sources, and addition of substances that increase citric acids production rate. Methanol has been suggested to increase citric acid fermentation on high carbohydrate containing substances. The objective of the study was to evaluate the suitability of sweet sorghum juice for citric acids production and to verify the effect of methanol on citric acids production using Aspergillus niger InaCC F539 as inoculant. Sweet sorghum juice with the total initial reducing sugar of 11.5 % (w/v) was used as the sole carbon sources. To study the effect of total initial reducing sugar on citric acid production the initial reducing sugar was adjusted to the concentration of 30 to 75 g/L. Preliminary experiment was conducted to get the optimum methanol concentration that stimulate citric acid production. The optimum methanol concentration that stimulate citric acid production was 4% (v/v). Submerged fermentation was conducted as shake culture (125 rpm at 28 °C). Citric acids production was affected by total initial reducing sugar. Higher total initial reducing sugar produced higher citric acids. Maximum citric acid production was 18.96g/L on sweet sorghum juice with 75 g/L total initial reducing sugar. Methanol 4 % (v/v) increase citric acid production by 41.35 to 65.89 %. Juice of sweet sorghum was a good medium for citric acids production, and methanol stimulate and increase citric acid production. It is a good basis for exploring efficient and cost effective industrial scale citric acid production. Keywords: Citric acid, Methanol, Sweet sorghum, Aspergillus niger